2018
DOI: 10.1021/acschembio.8b00402
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial MenJ: An Oxidoreductase Involved in Menaquinone Biosynthesis

Abstract: MenJ, annotated as an oxidoreductase, was recently demonstrated to catalyze the reduction (saturation) of a single double bond in the isoprenyl side-chain of mycobacterial menaquinone. This modification was shown to be essential for bacterial survival in J774A.1 macrophage-like cells, suggesting that MenJ may be a conditional drug target in Mycobacterium tuberculosis and other pathogenic mycobacteria. Recombinant protein was expressed in a heterologous host, and the activity was characterized. Although highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 45 publications
(112 reference statements)
1
45
0
Order By: Relevance
“…It should be noted that the catalytic rate is likely to be higher in the crowded native environment of the M. tuberculosis cell where Ddn and menaquinone are co-localised at the cell membrane [24]. The enzyme kinetics of Ddn are comparable to another mycobacterial menaquinone oxidoreductase, MenJ (Rv0561c), which is found in the menaquinone biosynthetic pathway (k cat /K M of~10 4 M -1 s -1 and K M of 30 μM [25]). The K M value is significantly lower than the median K M of enzymes with their native substrates (~130 μM), and the k cat /K M value is within the broad distribution of known enzymes (10 3 −10 7 M -1 s -1 ), albeit at the lower end of the range [26,27].…”
Section: The Physiological Role Of Ddnmentioning
confidence: 94%
“…It should be noted that the catalytic rate is likely to be higher in the crowded native environment of the M. tuberculosis cell where Ddn and menaquinone are co-localised at the cell membrane [24]. The enzyme kinetics of Ddn are comparable to another mycobacterial menaquinone oxidoreductase, MenJ (Rv0561c), which is found in the menaquinone biosynthetic pathway (k cat /K M of~10 4 M -1 s -1 and K M of 30 μM [25]). The K M value is significantly lower than the median K M of enzymes with their native substrates (~130 μM), and the k cat /K M value is within the broad distribution of known enzymes (10 3 −10 7 M -1 s -1 ), albeit at the lower end of the range [26,27].…”
Section: The Physiological Role Of Ddnmentioning
confidence: 94%
“…These enzymes catalyze the oxidation of NADH to NAD + and succinate to fumarate, respectively, followed by the menaquinone/menaquinol reduction. The menaquinone/menaquinol redox pool then transfers the electrons to a final acceptor (oxygen in aerobic conditions and nitrate or fumarate in anaerobic conditions) via terminal respiratory oxidases, while protons are pumped across the membrane, generating the PMF [ 17 , 18 , 19 ]. Despite an emerging role of fumarate reductase and nitrate reductase under hypoxia, in such conditions, the redox mediated by these enzymes is poorly understood, and a major focus is still given to the cytochrome bc1-aa3 “supercomplex” and the cytochrome bd oxidase, acknowledged to play a vital role in aerobic conditions.…”
Section: Energy-metabolism In Mycobacterium Tuberculosismentioning
confidence: 99%
“…It is well known that menaquinone (vitamin K2) plays an important role in producing the electrochemical gradient required for the production of ATP in ETC by shuttling electrons to terminal reductases. Therefore, each step involved in menaquinone biosynthesis, catalyzed by Men enzymes (MenA-J), is a potential chemotherapeutic target; besides, unlike bacteria, human cells are unable to produce menaquinone ex novo , as it is obtained only through the diet [ 17 , 18 , 19 ]. The most promising results come from inhibitors of Men-enzymes that function downstream of the synthesis pathway (MenA, MenB, MenG), of which DG70 is the most recent compound.…”
Section: Classification Of Drugs Targeting Energy-metabolism In mentioning
confidence: 99%
“…MenH/UbiE), forming menaquinone (Dhiman et al, 2009). Finally, the double bond in the β-isoprene unit of the polyprenyl chain is reduced by the reductase MenJ to form the mature product, such as MK-9 (II-H 2 ) (Upadhyay et al, 2015, 2018). Our comparative proteomic analysis of the IMD and the PM-CW suggested that MenG and MenJ are enriched in the IMD, while MenA was not detected in either the IMD or the PM-CW (Hayashi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%